Influence of plant ingredients on the composition of the spreads - Petrina, Alla; Tereshchenko, Anna; Bila, Galina (My University, 2015)
The article proves the advisability of using vegetable ingredients in the spreads formation. The content ofsolid triglycerides in the vegetable-fat blends with different amounts of milk thistle fruit-oil, and the addition ofCitri-Fi dietary fibers has been investigated. The influence of the above-mentioned fibers on the texture ofvegetable-fat blends, as well as the ability to preserve the ductility under mechanical stress and while storagehas been determined according to the hardness index. The obtained results are used to develop the spreadswith fillers technology.
Keywords: dietary fiber; харчові волокна; спред; spread; олія розторопші; milk thistle oil; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів